Low-velocity flexural impact response of steel fiber reinforced concrete subjected to freeze–thaw cycles in NaCl solution. (30th December 2015) - Zhang, Wuman; Chen, Shuhang; Zhang, Ning; Zhou, Yao
Highlights: The flexural impact performance, freeze–thaw and deicing salt resistance of steel fiber reinforced concrete (SFRC). Freeze–thaw cycles in the 3.0% NaCl solution of steel fiber reinforced concrete (SFRC). Flexural impact tests of steel fiber reinforced concrete (SFRC). The initial impact strength decreases obviously after the SFRC is subjected to 250 freeze–thaw cycles in 3.0% NaCl solution. Abstract: The flexural impact responses of steel fiber reinforced concrete (SFRC) with freeze–thaw cycles in 3.0% NaCl solution were investigated in this paper. Freeze–thaw cycles were carried out and followed by the flexural impact test. The weight loss and the residual strain of SFRC were measured, respectively. The results show that 1.5% (by volume) steel fibers addition has a little effect on the weight loss of concrete subjected to the freeze–thaw cycles in 3.0% NaCl solution. Both the bottom and side residual strain increase with the increasing of flexural impact test. For SFRC subjected to 0, 100, 150, 200 freeze–thaw cycles, the relationships between the residual strain and the number of impact test can be fitted by exponential functions with a good correlation coefficient. The effect of freeze–thaw cycles in 3.0% NaCl solution on the initial impact strength is slight. However, the initial impact strength decreases obviously after SFRC specimens are subjected to 250 freeze–thaw cycles.